Development of pH indicator film containing butterfly pea flower (Clitoria ternatea L.) anthocyanin using locust bean gum/unbleached wheat flour matrix - Hasanah, Nur Nabilah; Azman, Ezzat Mohamad; Rozzamri, Ashari; Zainal Abedin, Nur Hanani; Ismail-Fitry, Mohammad Rashedi (Elsevier B.V., 2025)
The growing interest in environmentally friendly packaging and smart food monitoring systems has driven the development of biodegradable films with pH-sensitive indicators. Among various biopolymers, natural gums and plant-based flours are being explored due to their film-forming abilities and biodegradability. In particular, locust bean gum (LBG) and unbleached wheat flour (UWF) exhibit potential due to their functional properties and abundance. This study aimed to determine the optimal film produced from LBG and UWF infused with anthocyanin from butterfly pea flower (BPF) extract, as a smart pH indicator. LBG's side branches can create a strong synergistic interaction with UWF, making it a promising matrix for producing pH indicator films. Films comprising 100 % LBG (L1), 100 % UWF (U1), 50 % LBG + 50 % UWF (LU), 70 % LBG + 30 % UWF (L2), and 30 % LBG + 70 % UWF (U2) were formulated. The physicochemical and microstructural characteristics of the different formulations were analysed. The pH indicator film containing 70 % LBG (L2) demonstrated greater stability, with lower moisture content (3.22 %), improved swelling properties (56.06 %), increased thickness (0.31 mm), strong water vapour permeability (3.87 × 10⁻⁶ g·s⁻¹·m⁻¹·Pa⁻¹), high tensile strength (0.82 MPa), and good elongation at break (57.75 %) in comparison to the other films. Furthermore, the microstructural properties of L2 exhibited a compact and dense structure compared to the other films. L2 also displayed visible colour changes across various pH levels (1.0–13.0). In conclusion, L2 film demonstrated balanced characteristics, making it the most suitable film for selection as a pH indicator film with immobilised BPF anthocyanin, and proved its effectiveness as a freshness indicator when applied to silver pomfret samples.